The Effect of Live Streaming and Online Customer Review on Purchase Decisions Through Trust as an Intervening Variable (Study on Shopee Users in Malang City) - Salim, Agus; Bushiri, Moh. Imam; hidayati, Nur (Dinasti Publisher, 2025)
The internet has developed into a lifestyle for people. Its use is not limited to obtaining and accessing information only, but to fulfill various needs. The change in people's lifestyles from offline shopping has led to a significant increase in the e-commerce market. Various marketplaces such as Shopee began to offer various kinds of convenience to meet the needs of the community by shopping online. Changes and developments in technology have made changes in customer behavior from purchasing through offline shops to through online shops or through e-commerce and marketplaces, this also affects purchasing decisions in buying a product or service.In this study, researchers used the explanatory method using a quantitative approach. The population of this study were Shopee users in Malang City who had made at least one purchase transaction. The data collection technique is by distributing questionnaires. The sample for this research was taken using purposive sampling technique with Malhotra's formula, which amounted to 70 respondents at Shopee users in Malang City. The variables in this study are Live Streaming (X1), Online Customer Review (X2), Purchase Decision (Y) and Trust (Z). The data analysis method used is validity test, reliability test and PLS test or Partial Least Square with the help of smart PLS software version 3. 0.The results of this study indicate that Live Streaming has a significant effect on Trust, Online Customer Review has a significant effect on Trust, Live Streaming has a significant effect on Purchasing Decisions, Online Customer Reviews has a significant effect on Purchasing Decisions, Trust has a significant effect on Purchasing Decisions. In indirect effects, it was also found that the results that Live Streaming on Purchasing Decisions did not mediate Trust were rejected and Online Customer Review on Purchasing Decisions mediated Trust was accepted.